Pituitary dysfunction in granulomatosis with polyangiitis - Vega-Beyhart, Arturo; Medina-Rangel, Irene Rocío; Hinojosa-Azaola, Andrea; Fernández-Barrio, Milagros; Vargas-Castro, Ana Sofía; García-Inciarte, Lucía; Guzmán-Pérez, Alberto; Torres-Victoria, Tania Raisha; Martínez-Sánchez, Froylán David; Pérez-Guzmán, Mireya Citlali; Hinojosa-Amaya, José Miguel; León-Suárez, Andrés; et al. (Clinical rheumatology, 2020)
Granulomatosis with polyangiitis (GPA) is a necrotizing granulomatous vasculitis of small vessels that affect the pituitary gland in less than 1% of cases being exceptionally rare. To describe the clinical, biochemical, radiological findings, treatment, and outcomes of 4 patients with GPA-related hypophysitis. A systematic review of published cases with the same diagnosis is presented as well. A cross-sectional case series of patients with hypophysitis due to GPA from 1981 to 2018 at a third level specialty center. Literature review was performed searching in seven different digital databases for terms “granulomatosis with polyangiitis” and “pituitary gland” or “hypophysitis,” including in the analysis all published cases between 1950 and 2019 with a minimum follow-up of 6 months. We found 197 patients with GPA in our institution of whom 4 patients (2.0%) had pituitary involvement. Clinical characteristics and outcomes are described. We also reviewed 7 case series, and 36 case reports describing pituitary dysfunction related to GPA from 1953 to 2019, including the clinical picture of an additional 74 patients. Pituitary dysfunction due to GPA is rare. Treatment is targeted to control systemic manifestations; nevertheless, the outcome of the pituitary function is poor. Central diabetes insipidus, particularly in younger women with other systemic features, should raise suspicion of GPA. Key Points • Involvement of the pituitary gland is an uncommon manifestation in GPA patients. The presence of central diabetes insipidus in the setting of systemic symptoms should prompt its suspicion. • In patients with pituitary involvement due to GPA, affection of other endocrine glands is rare, neither concomitant nor in different times during the disease course. This may arise the hypothesis of a local or regional pathogenesis affection of the gland. • There is no consensus on the best therapy strategy for GPA hypophysitis. Although the use of glucocorticoids with CYC is the most common drug combination, no differences in the outcome of the pituitary function and GPA disease course are seen with other immunosuppressants. • Poor prognosis regarding pituitary function is expected due to possible permanent pituitary tissue damage that results in the need of permanent hormonal replacement.